Gas Bearings: Modelling, Design and Applications - Raparelli, Terenziano; Colombo, Federico; Trivella, Andrea; Lentini, Luigi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the modelling and the design process of gas bearings, on the experimental validation of such models, and on their applications. In particular, recent developments about foil bearings, aerostatic bearings, porous bearings, and non-contact precision positioning systems are shown.